2019
DOI: 10.1021/acs.jafc.8b06656
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Key Aroma Compounds in Two Differently Dried Toona sinensis (A. Juss.) Roem. by Means of the Molecular Sensory Science Concept

Abstract: A systematic approach for the characterization of the key aroma-active compounds in sun-dried Toona sinensis (SDTS) and vacuum-dried T. sinensis (VDTS) was performed by means of the molecular sensory science concept. A total of 64 aroma-active compounds were identified via gas chromatography−olfactometry (GC-O) and gas chromatography−mass spectrometry (GC-MS). Aroma extract dilution analysis (AEDA) and static headspace dilution analysis revealed 39 odorants in SDTS and 32 odorants in VDTS with flavor dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 41 publications
4
57
0
2
Order By: Relevance
“…Its economic importance can exemplarily be seen in the fact that >1 million people are actually working on T. sinensis products in China. Its planting area is >1 billion square meters and cultivating >800 billion kg of T. sinensis sprouts per year (Zhai and Granvogl 2019). However, there is little genomic information has been reported.…”
mentioning
confidence: 99%
“…Its economic importance can exemplarily be seen in the fact that >1 million people are actually working on T. sinensis products in China. Its planting area is >1 billion square meters and cultivating >800 billion kg of T. sinensis sprouts per year (Zhai and Granvogl 2019). However, there is little genomic information has been reported.…”
mentioning
confidence: 99%
“…Liu et al . (2013), Yang et al ., (2019) and Zhai & Granvogl (2019, 2020) reported that the sulphide‐containing compounds in TS shoots are not stable. They could be degraded or converted to form other sulphur‐containing compounds through a series of reactions, such as (Z,Z)‐di‐1‐propenyl disulphide, cis‐ and trans‐2‐mercapto‐3,4‐dimethyl‐2,3‐dihydrothiophene.…”
Section: Resultsmentioning
confidence: 99%
“…Odor descriptions Reference Alcohols (E)-2-hexenol green, fruity [15] 1-butanol overall flavor, sweet aroma [16] 1-hexanol fresh, green, earthy [16] 1-octen-3-ol mushroom [16] 3-mercaptohexan-1-ol sulfur and passion fruit [17] 3-octanol earthy, mushroom, herbal [18] benzyl alcohol bitter almond-like, fruity [19] benzeneethanol flowery, floral, vegetal, woody [20] linalool citrus-like, flowery [15] furaneol sweet, caramel, candy [20] methanethiol sulfur, gasoline, and garlic [21] nonanol rose-orange octanol jasmine, lemon [21] menthol mint-like [15] Aldehydes (E)-2-heptenal green, leaf, and fat [17] (E)-2-octenal green and leaf [17] 3-methylbutanal malty [16] benzaldehyde sweet, fruity, roasted, almond, fragant, burnt sugar [21] phenylacetaldehyde sweet and fruity [17] heptanal green [21] hexanal green, grassy [22] furfural bread, almond, and sweet [17] nonanal fat, citrus, green, fruity [21] octanal fat, citrus, and green [17] (E)-2-octenal green and leaf [17] pentanal almond, malt, pungent [20] octanal green, fruity, orange, citrus [20] vanillin vanilla-like, sweet [15] decanal sweet, aldehydic, waxy [18] nonanal waxy, aldehydic, rose [18] Acids propanoic acid sour-like, sweaty [15] acetic acid sour [17] hexanoic acid sweaty, sour, cheesy [20] butyric acid sour and stink [21] decanoic acid soapy, musty [15] Volatile compounds Odor descriptions Reference nonanoic acid moldy, pungent [15] Esters ethyl 2-methylbutanoate fruity [20] γ-octalactone sweet, coconut, and peach…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Odor descriptions Reference Alcohols Ketones 2,3-butanedione butter [17] 2,3-pentanedione butter [17] 2-heptanone fruity, sweet, herbal [18] 3-hydroxy-2-butanone butter [17] β-damascenone sweety and floral [16] β-ionone flowery, violet-like [15] acetophenone musty and almond [17] nootkatone fruity [20] carvone minty, licorice [18] Pyrazines 2,3,5-trimethylpyrazine roast and musty [17] 2-methoxy-3,5-dimethylpyrazine roast and musty [17] 2,5-dimethylpyrazine nutty and roasted [17] 2-methylpyrazine roast [17] 2,6-dimethylpyrazine nutty and roasted [15] Others α-pinene pine, plant [17] Volatile compounds Odor descriptions Reference D-Limonene citrus-like [16] α-terpinolene fruity, green [20] valencene citrus-like [20] dimethyl sulfide cabbage, sulfur, and corn [17] difurfuryl sulfide roasted [17] 2-acetylfuran sweet, almonds, and roasted [17] 2-ethylfuran rubbery, pungent, sweet [20] benzothiazole sulfury, rubbery, vegetable [18] Generally, GC-MS is mainly applied to establish the volatile fingerprint and determine the aroma contents of fruits and vegetables. The qualitative identification of aroma compounds generally uses database search, standard products and retention index methods.…”
Section: Volatile Compoundsmentioning
confidence: 99%